Constrained interpolation using rational cubic spline with three parameters - Samsul Ariffin Abdul Karim,; Mohammad Khatim Hasan,; Ishak Hashim, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The C1 rational cubic spline function (cubic/quadratic) with three parameters is used to construct a constrained interpolating curve that lies below or above an arbitrary straight line or between two straight lines. The data dependent sufficient conditions for the rational cubic interpolant bounded by two straight lines are derived on one parameter, while the other two are free parameters that will be useful for shape modification. Some numerical results will be presented by using Mathematica software. Comparison with some existing schemes shows that the proposed scheme outperforms the existing schemes.